Pengaruh Pemasaran Produk Air Minum Isi Ulang Terhadap Kualitas Produk Melalui Kepuasan Pelanggan Sebagai Variabel Intervening ( Di Usaha Dagang Hafizah) - Aldiansyah Aldiansyah; Yulia Tiara Tanjung; Wira Wahyuni (Departement of Mathematics Education, 2023)
The purpose of this study is to analyze the effect of marketing on customer satisfaction partially or simultaneously, analyze the influence of marketing on quality partially or simultaneously, analyze the direct and indirect influence of marketing on quality through intervening variables of customer satisfaction. The type of causal associative quantitative research, the population used was 150 customers at the Hafizah Water Refillable Drinking Water Depot, while the number of samples used in the study was 109 respondents. Data collection in this study is a questionnaire with a Likert scale, filling out the questionnaire is that respondents are asked to give opinions about a series of statements related to the object being studied in the form of values. The test tool used is path analysis with SPSS 29 program application tools. The results of this study show that partial and simultaneous marketing has a positive and significant influence on customer satisfaction at the Hafizah Water refillable drinking water depot, marketing also partially or simultaneously has a positive and significant influence on the quality of the Hafizah Water refillable drinking water depot, and indirectly marketing on quality through customer satisfaction as an intervening variable has a significant influence on quality at Hafizah Water refillable drinking water depot.